Testing of speed-strength readiness of skiing athletes using intelligent sensory-based systems - Vassiouk, V.; Darozhka, A.; Minchenya, A. (Sporto Mokslas-Sport Science, 2019)
This paper shows the aprobation attempt of mobile intelligent sensory-based systems application to assess the performance of technical readiness and the level of speed-strength qualities development of athletes in ski locomotions. The evaluation was subjected to an athlete`s ability to generate propulsive forces during the interaction between the ski poles and the bearing area. The study involved two athletes, who, while using only double poling techniques of skiing, performed control treadmill roller skiing test. An innovative mobile sensory-based system based on wireless tensometry was used to record the poling forces. The essence of the method of recording efforts was to fix ski poles intelligent sensors "SKI-Smart" developed in the Sports biomechanics laboratory of the Belarusian National Technical University. Determination of key points of movement cycle phases was carried out by correlating graphs of ski poles elastic deformation with video data of the exercise performance. While mathematically processing the obtained data, characterizing indicators of the effectiveness of skiing locomotions were calculated: the duration of the cycle, the duration (t, c) and the ratio of the key skiing locomotions phases, the force (F) applied by an athlete to the ski poles, the work (A), the power (N) for the entire control segment and for each movement cycle separately, and indicators reflecting the angular characteristics of movements. According to the results of the study, differences in kinetic and kinematic characteristics of motor actions were revealed, a conjugate assessment of the technique of movements and speed-strength readiness of athletes in the structure of the main competitive exercise were made. The use of smart sensors "SKI-Smart" enables operational correction of the most important components of the movement technique in ski locomotion. Thus, one can select the appropriate training tools aimed at increasing the level of speed-strength preparedness of athletes.